2012
DOI: 10.1007/s10735-012-9437-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological study of small Rho GTPases and β-catenin during regeneration of the rat submandibular gland

Abstract: Our study immunohistochemically evaluated the localization patterns of small Rho GTPases and β-catenin during regeneration of the rat submandibular gland. After 7 days of obstruction, regenerating glands were collected at days 0, 3, 7, 11 and 14 after duct release to study regeneration. RhoA was detected strongly and RhoC was detected weakly in the cytoplasm of newly formed acinar cells from day 3 to 7, and both RhoA and RhoC at the basal site and cytoplasm were detected moderately from day 11 to 14. RhoB was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Histologically, atrophy and disappearance of acinar cells, and gradual increases in duct-like structures and fibrous connective tissue were observed. Changes in salivary gland tissue after short-term ligation that have been reported include enlargement of duct lumens, atrophy and disappearance of acinar cells above the ligation, increases in ductlike structures and proliferation of fibrous connective tissue, degranulation and vacuolar degeneration of granular duct cells and acinar cells, and disappearance of basal striations from the striated duct [8][9][10][11][12][13][14][15][16][17][18] . This was similar to findings in the long-term ligation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histologically, atrophy and disappearance of acinar cells, and gradual increases in duct-like structures and fibrous connective tissue were observed. Changes in salivary gland tissue after short-term ligation that have been reported include enlargement of duct lumens, atrophy and disappearance of acinar cells above the ligation, increases in ductlike structures and proliferation of fibrous connective tissue, degranulation and vacuolar degeneration of granular duct cells and acinar cells, and disappearance of basal striations from the striated duct [8][9][10][11][12][13][14][15][16][17][18] . This was similar to findings in the long-term ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies of atrophied salivary glands have reported the occurrence of duct-like structures 17,18,[29][30][31] . Duct-like structures resulting from ligation were also observed in the present study, and it was shown that these increase over time with long-term ligation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated tissue changes in the glandular parenchyma as a result of ligation of the main excretory duct of the submandibular gland; all have reported acinar cell atrophy, increase in interlobular connective tissue, and enlargement of the lumina as histological changes [6][7][8][9][10][11][12][13] . Here we investigated the expression of the water channel protein AQP5, a marker for acinar cells [14][15][16] , in mice and of the secretase α-amylase 17,18) after different periods of ligation to evaluate the function of residual acinar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary gland tissue can be damaged by conditions such as sialadenitis, sialolithiasis, trauma, and radiation therapy, which can lead to degeneration, atrophy, and necrosis. Methods to examine these pathological conditions include surgical resection [1][2][3], duct ligation [4][5][6], radiation [7,8], laser irradiation [9,10], and histopathological and immunohistochemical analysis.…”
Section: Introductionmentioning
confidence: 99%